2003
DOI: 10.1074/jbc.m301028200
|View full text |Cite
|
Sign up to set email alerts
|

37-kDa Laminin Receptor Precursor Modulates Cytotoxic Necrotizing Factor 1–mediated RhoA Activation and Bacterial Uptake

Abstract: Cytotoxic necrotizing factor 1 (CNF1) is a bacterial toxin known to activate Rho GTPases and induce host cell cytoskeleton rearrangements. The constitutive activation of Rho GTPases by CNF1 is shown to enhance bacterial uptake in epithelial cells and human brain microvascular endothelial cells. However, it is unknown how exogenous CNF1 exhibits such phenotypes in eukaryotic cells. Here, we identified 37-kDa laminin receptor precursor (LRP) as the receptor for CNF1 from screening the cDNA library of human brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 38 publications
2
124
0
Order By: Relevance
“…118 Interestingly, some microorganisms, through the release of adhesion molecules, bind to fibronectin and activate Rho GTPases to promote host cell invasion. 119 For instance, the bacterial fibronectin-binding protein of Campylobacter jejuni, CadF, and the intact flagellum are involved in eukaryotic Rac1 GTPase activation and host cell invasion. 116,120 It has been postulated that CadF binding to fibronectin results in integrin clustering and activation.…”
Section: Treponema Pallidummentioning
confidence: 99%
“…118 Interestingly, some microorganisms, through the release of adhesion molecules, bind to fibronectin and activate Rho GTPases to promote host cell invasion. 119 For instance, the bacterial fibronectin-binding protein of Campylobacter jejuni, CadF, and the intact flagellum are involved in eukaryotic Rac1 GTPase activation and host cell invasion. 116,120 It has been postulated that CadF binding to fibronectin results in integrin clustering and activation.…”
Section: Treponema Pallidummentioning
confidence: 99%
“…We have previously shown that the E. coli K1 invasion of HBMEC is the result of interactions of bacterial structures with their respective HBMEC receptors (Kim 2003). For example, E. coli K1 proteins, such as IbeA and cytotoxic necrotizing factor (CNF) 1, contribute to the invasion of HBMEC and interact with specific receptors present on HBMEC, a 45-kDa protein and 69LR, respectively (Nemani et al 1999a;Chung et al 2003). We have also shown that FimH, one of the E. coli structures contributing to the binding to and invasion of HBMEC is able to induce Ca 2+ changes in HBMEC through its interaction with the putative CD48 receptor: preincubation of HBMEC with FimH or CD48 antibody prevents subsequent CD48-induced or FimH-induced [Ca 2+ ] i changes, respectively (Khan et al 2007).…”
Section: Sources Of Intracellular Ca 2+ Elevation and Their Contributmentioning
confidence: 99%
“…Recently, we have demonstrated that the GBS pilus protein PilA and Srr-1 interact with components of the host extracellular matrix (ECM) to promote BBB interactions and the development of meningitis (8,9). Other meningeal pathogens, such as Streptococcus pneumoniae (SPN), E. coli K1, Neisseria meningitidis, and Haemophilus influenza type B (HiB, also bind ECM components and ECM receptors (e.g., integrins and laminin receptor) to mediate bacterial-BBB interactions (12)(13)(14)(15). Given that host ECM components and receptors preferentially localize to the basolateral surface of polarized BBB endothelium (16), we hypothesized that disruption of junctional protein complexes in brain endothelium is the first step leading to bacterial access to basally expressed receptors.…”
Section: Introductionmentioning
confidence: 99%